x x x ⋅ ⋅ ⋅
The iterated exponentiation above equals 1 when x = 1 .
The same expression can have a value of __________ for some real number x .
Fill in the blank.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let y = x x x ⋅ ⋅ ⋅ . Then y = x y . We note that x = y y is a solution, since y = ( y y ) y . The means that x = 1 , 2 , 3 3 , 4 4 , 5 5 , ⋯ are likely solutions when the values of y = 1 , 2 , 3 , 4 , 5 , ⋯ respectively. But for y to converge Lambert W-function (see equation 13) requires that e − e ≤ x ≤ e e 1 ≈ 0 . 0 6 5 9 ≤ x ≤ 1 . 4 4 4 6 , and only x = 1 , 2 fall into the range and therefore, the other value of y = 2 .
Problem Loading...
Note Loading...
Set Loading...
Suppose the iterated exponentiation (we'll call it a 'power tower' from now on) converges to a finite value, call it y . We will assume that both x and y are positive; the power tower does not appear (to me) to yield real numbers for any negative values other than x = − 1 (anyone know whether that is indeed the case?) and at that value it's easy to see that y = − 1 . So
x x x ⋅ ⋅ ⋅ = y
Since both sides are finite, we can use them as exponents of x , i.e.
( x ) x x x ⋅ ⋅ ⋅ y y y 1 = ( x ) y = x y = x
We derive the left side:
d y d ( y y 1 ) = d y d ( e y 1 ln y ) = e y 1 ln y d y d ( y 1 ln y ) = y y 1 ( y 2 1 − ln y )
This yields the critical value y = e . We note that lim y → 0 + y y 1 = 0 ; also, lim y → ∞ y y 1 = 1 (see note below). Since e e 1 > 1 , we have that y y 1 has an absolute maximum when y = e , which means that our power tower can only converge for x ≤ e e 1
It's not difficult to see that for 0 < x ≤ 1 , the power tower is bounded above by 1 ; for 1 < x ≤ e e 1 , it seems intuitively obvious that the power tower is a strictly increasing function, and therefore it will achieve its maximum value at the maximum value of x for which it converges. If we assume it does converge for x = e e 1 , say to L , then ( e e 1 ) L = L , and by inspection we would have L = e . Unfortunately we haven't, strictly speaking, proven convergence at x = e e 1 ; also, when deriving y it is not immediately obvious that y ′ is strictly positive for 1 < x ≤ e e 1
So instead, for 1 < x ≤ e e 1 , we define a sequence by a 1 = x and a n + 1 = x a n ; then y = lim n → ∞ a n . We can show by induction that { a n } is bounded above by e . We have a 1 ≤ e e 1 ≤ e ; and if a n ≤ e , then a n + 1 = x a n ≤ ( e e 1 ) e = e . Thus our power tower cannot yield values higher than e , so the last three answer choices are not possible; it's not difficult to see that x = 2 yields the only possible answer y = 2
Note: to calculate lim y → ∞ y y 1 , we let z = y y 1 . Then
ln z y → ∞ lim ln z = y 1 ln y = y → ∞ lim y ln y = y → ∞ lim 1 y 1 [Applying L’H o ˆ pital’s Rule] = 0
Then
y → ∞ lim y y 1 = y → ∞ lim z = y → ∞ lim e ln z = e 0 = 1